Effects of knowledge of results and change-oriented feedback on swimming performance - Doma, K.; Engel, A.; Connor, J.; Gahreman, D. (International Journal of Sports Physiology and Performance, 2022)
Purpose: This study examined the effect of providing knowledge of results (KR) with, and without, promotion- and change-oriented feedback on repeated-sprint ability in swimmers.